psychological experiences of patients with COVID-19: A qualitative study. - حسن نسرين; فاطمة قريط; مالك حجازية (Latakia University Journal -Medical Sciences Series, 2023)
Objective: This study aims to know the psychological experiences of patients with CO VID-19during their stay in the hospital isolation wards. Research Materials and Methods: A descriptive phenomenological study, data were collected by conducting interviews with 15 patients discharged from hospitals after receiving treatment for COVID-19 in isolation. Patients were selected using the purposive sample method and snowball sample from Al-Haffa Hospital and Tishreen University Hospital in Lattakia during the period between July 10-December 10, 2022. The data were analyzed using (Colizzi). Results: The results of the current study identified seven main groups that reflected psychological experiences of novel coronavirus disease-19. They are: fear, anxiety, sadness, frustration, loneliness, guilt, and low self-esteem. Conclusion: Corona virus patients suffered from complex psychological experiences during their stay in the hospital in the isolation department, so the patient care plan must include an early and accurate assessment of the psychological needs of patients, and thus make appropriate interventions to prevent the development of these problems to dangerous levels and thus deteriorate conditions and delay recovery. Recommendations: The study recommends focusing on the psychological aspect of treatment, and conducting research to develop appropriate tools to accurately identify the psychological problems of patients, and thus find appropriate ways to deal with these problems.